2017
DOI: 10.1039/c7ra01185g
|View full text |Cite
|
Sign up to set email alerts
|

The impact of zeta potential changes on Ceratium hirundinella cell removal and the ability of cells to restore its natural surface charge during drinking water purification

Abstract: Unit processes of a conventional water purification facility are designed to remove suspended material from source water (both inorganic and organic impurities). Organic substances in source water include phytoplankton species (algae and cyanobacteria) that are generally negatively charged on the surface of the cells. The zeta potential (ZP) of algal cells needs to be destabilized in order to enhance removal thereof during water purification. The aims of this study were to investigate the ZP changes of Ceratiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…PA (nylon 6, 6) is known to be positively charged, whereas typical plastic materials such as PE and PS tend to be negatively charged in triboelectric series (Liu et al 2015 ; Kim et al 2017 ). Algal cells are also known to be negatively charged (Ewerts et al 2017 ). It has been demonstrated that positively charged PS particles (20–50 nm) have a higher binding affinity toward algal cells, which produces a greater effect on the cells than negatively charged PS particles (Bergami et al 2017 ; Nolte et al 2017 ; Bhattacharya et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…PA (nylon 6, 6) is known to be positively charged, whereas typical plastic materials such as PE and PS tend to be negatively charged in triboelectric series (Liu et al 2015 ; Kim et al 2017 ). Algal cells are also known to be negatively charged (Ewerts et al 2017 ). It has been demonstrated that positively charged PS particles (20–50 nm) have a higher binding affinity toward algal cells, which produces a greater effect on the cells than negatively charged PS particles (Bergami et al 2017 ; Nolte et al 2017 ; Bhattacharya et al 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…The differing surface charges and zeta potentials of green algae, cyanobacteria and diatoms may have been a factor in their responses to the EMF treatment. The surface charge among green algae, cyanobacteria and diatoms differs in their composition although they are all negatively charged (Ewerts et al 2017). Zeta-potential is indicated by a particles surface charge and in this context is the measurement of the electrostatic potential at an organism's surface membrane with the surrounding solution (Clogston and Patri, 2011;Vogel et al 2017).…”
Section: Phytoplankton Composition Response To Emf Treatmentmentioning
confidence: 99%
“…PA (nylon 6, 6) is known to be positively charged, whereas typical plastic materials such as PE and PS tend to be negatively charged in triboelectric series (Liu et al 2015;Kim et al 2017). Algal cells are also known to be negatively charged (Ewerts et al 2017). It has been demonstrated that positively charged PS particles (20-50 nm) have a higher binding a nity toward algal cells, which produces a greater effect on the cells than negatively charged PS particles (Bergami et al 2017;Nolte et al 2017;Bhattacharya et al 2010).…”
Section: Adhesion Of R Subcapitata Cells and Nylon Particlesmentioning
confidence: 99%